Role of the heat shock protein family in bone metabolism - Hang, Kai (Cell Stress Chaperones, 2018)
Heat shock proteins (HSPs) are a family of proteins produced by cells in response to exposure to stressful conditions. In addition to their role as chaperones, they also play an important role in the cardiovascular, immune, and other systems. Normal bone tissue is maintained by bone metabolism, particularly by the balance between osteoblasts and osteoclasts, which are physiologically regulated by multiple hormones and cytokines. In recent years, studies have reported the vital role of HSPs in bone metabolism. However, the conclusions remain largely controversial, and the exact mechanisms are still unclear, so a review and analyses of previous studies are of importance. This article reviews the current understanding of the roles and effects of HSPs on bone cells (osteoblasts, osteoclasts, and osteocytes), in relation to bone metabolism.